2023
DOI: 10.1002/cam4.6295
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram for predicting the rapid progression of diffuse large B‐cell lymphoma established by combining baseline PET/CT total metabolic tumor volume, lesion diffusion, and TP53 mutations

Cong Liu,
Pengyue Shi,
Zhenjiang Li
et al.

Abstract: ObjectivesThis study aimed to integrate positron emission tomography/computed tomography (PET/CT) metrics and genetic mutations to optimize the risk stratification for diffuse large B‐cell lymphoma (DLBCL) patients.MethodsThe data of 94 primary DLBCL patients with baseline PET/CT examination completed in the Shandong Cancer Hospital and Institute (Jinan, China) were analyzed to establish a training cohort. An independent cohort of 45 DLBCL patients with baseline PET/CT examination from other hospitals was esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“… 30 , 31 Of note, TP53 Mut was an independent prognostic factor of PFS and OS, representing a distinct subtype with inferior prognosis irrespective of IPI score. 5 , 32 Less likely to benefit from R-CHOP–based immunochemotherapy, 33 , 34 , 35 novel targeted therapies, such as decitabine, 19 are required for patients with TP53 Mut , even stratified as low-risk IPI. Furthermore, our study demonstrated that integrating TP53 Mut into the IPI enhanced its capacity to differentiate patient survival outcomes, which has also been validated by external cohorts.…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 Of note, TP53 Mut was an independent prognostic factor of PFS and OS, representing a distinct subtype with inferior prognosis irrespective of IPI score. 5 , 32 Less likely to benefit from R-CHOP–based immunochemotherapy, 33 , 34 , 35 novel targeted therapies, such as decitabine, 19 are required for patients with TP53 Mut , even stratified as low-risk IPI. Furthermore, our study demonstrated that integrating TP53 Mut into the IPI enhanced its capacity to differentiate patient survival outcomes, which has also been validated by external cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Taking the above into consideration, novel predictive scores are being established that include TP53 abnormalities in combination with other biological and clinical markers. In one study, PET/CT data from DLBCL patients and a targeted NGS panel consisting of 43 commonly mutated genes were employed to devise a prognostic score [ 117 ]. Among the different variables, the pretreatment total metabolic tumor volume, the largest distance between two lesions standardized by body area, and the presence of TP53 mutations emerged as the most important factors for risk stratification and inferior PFS, displaying better accuracy than current clinical scores.…”
Section: Prognostic Significance Of Tp53 Alteratio...mentioning
confidence: 99%